Dietary Components and Immune Function - Watson, Ronald Ross.; Watson, Ronald Ross.; Zibadi, Sherma.; Zibadi, Sherma.; Preedy, Victor R.; Preedy, Victor R. (Nutrition and Health, 2010)
Dietary Components and Immune Function focuses on immune modulation, immune mediated disease resistance, immune changes due to AIDS, immune modulated cancer therapy, and autoimmune diseases as modified by dietary supplement, bioactive foods and supplements. The potential value of such approaches in maintaining wellness and preventing disease are addressed by examining their effects in vitro and in vivo on innate and adaptive immune responses. Emerging fields of science and important discoveries relating to early stages of new nutriceuticals in cancer prevention, prior to clinical trials are also covered. This volume represents a single source of material related to nutriceuticals and their constituents as they relate to cancer therapy and prevention. As such the book will be essential reading for nutritionists, pharmacologists, health care professionals, research scientists, cancer workers, pathologists, molecular or cellular biochemists, physicians, general practitioners as well as those interested in diet and nutrition in disease resistance via immune regulation.